Bariery w randkowaniu kobiet z niepełnosprawnością ruchową - Zawiślak, Agnieszka (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
The article addresses the issue of dating barriers of women with physical disability. This phenomenon was presented with reference to available research results and analysis. Dating barriers were described considering division of external and internal barriers. External barriers considered social issues which encompassed negative stereotypes, patterns, attitudes and architectural barriers. Internal barriers related directly women with physical disability including their attitudes towards oneself, self-esteem and social skills. The analysis showed that the women with physical disability may have more difficulty in finding partners and forming personal relationships leading to intimacy than do women without disabilities.